Measured and simulated interactions between Kenaf Geogrid Limited Life Geosynthetics (LLGs) and Silty Sand Backfill - T. Tanchaisawat (2018)
New types of natural fiber reinforcing materials have been introduced recently in geotechnical applications; for example, jute, coir, sugarcane bagasse. Natural fibers can be modified into woven geogrid and used in geotechnical engineering applications and generally classified as Limited Life Geosynthetics (LLGs). The natural fiber used for this study was roselle or Thai Kenaf which was made into geogrid with opening size of 4 mm was investigated. Locally available silty sand was used for compacted backfill material. Large scale pullout and direct shear tests were performed in order to investigate interaction mechanism of kenaf geogrid and compacted sand. Numerical simulation was studied in terms of its reinforcement mechanism on plane strain mode. From the results of sensitivity analyses, the interaction coefficient and axial stiffness of the geogrid were found to be important parameters affecting the efficiency of geogrid. The interaction coefficient R inter is 0.9 for pullout mechanism and 0.6 for direct shear mechanism. The recommended parameters for these reinforced systems have been introduced to use as sustainable geosynthetics. Furthermore, Kenaf geogrid which is LLGs concept can be widely promoted for natural fiber application in many countries.